Development of Klaisu Village AS a Sustainable Tourism Village: Natural Potential, Culture, and Infrastructure Challenges - Siane, Siane Florince Siwa; Awayanti Srem, Ade Irma; Qui, Frendly (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The development of tourism villages is one of the strategies to improve the local economy, especially in areas that have great natural and cultural potential. Klaisu Village, located in Jayapura Regency, has great potential to be developed as a sustainable tourism village, but still faces challenges in terms of infrastructure and limited community knowledge in tourism management. This research aims to identify the potential, challenges, and development strategies of Klaisu Village as a sustainable tourism village. This research used a descriptive qualitative approach with a case study method. The population of this study consisted of Klaisu Village community involved in the tourism sector, using purposive sampling technique. The research sample totalled 15 informants consisting of the village head, tourism managers, and people directly involved in the tourism business. The research was conducted in Klaisu Village, Jayapura Regency, Papua, for three months, from October to December 2024. The results showed that Klaisu Village has tremendous natural potential, but limited infrastructure is the main obstacle. In addition, the development of tourism based on cocoa, coffee and vanilla farming also has great opportunities, but requires improving community skills in tourism management and environmental conservation. The implication of this research is the importance of collaboration between the government, community, and private sector to support the development of sustainable tourism villages.